Responses of Eucalyptus benthamii seedlings to the application of the organic fertilizer Bacsol - Riboldi Monteiro, Pedro Henrique; Winagraski, Etienne; Kaschuk, Glaciela; Gaiad, Sérgio; Marques, Renato; Garcia Auer, Celso (BOSQUE, 2017)
Eucalyptus benthamii is a tree species commonly planted in subtropical areas, including the Southern Brazil, due to its tolerance to low temperatures and frosts. The success of E. benthamii plantation depends on the seedlings vigor during transplantation. We hypothesized that improvement of chemical and biological properties of growth substrate would produce more vigorous E. benthamii seedlings. Thus, we applied increasing doses (0, 0.5, 1.0, 1.5 and 2.0 g per seedling) of the organic fertilizer Bacsol, which carries a consortium of potential plant growth promoting microorganisms, on the substrate, and measured the growth and development of E. benthamii seedlings. Two experiments were performed in 2011 and 2012. The first experiment included measurements in four growth stages to estimate the relative growth rates. The second one ended at the time that seedlings reached standard heights for transplantation (about ± 20 cm). Measurements on plant height, stem diameter, shoot dry weight and relative growth rates indicated that the application of Bacsol improved E. benthamii seedlings vigor and decreased the time needed in nursery, from 150 days to 90 days. The best responses occurred at doses from 1.3 g to 1.5 g per seedling. The data demonstrated that application of Bacsol in substrate is a promising technology to increase E. benthamii seedlings vigor.